Direct transcriptional repression of the genes encoding the zinc-finger proteins Gfi1b and Gfi1 by Gfi1b - Vassen, Lothar (Oxford University Press, 2005)
Gfi1b is a 37 kDa transcriptional repressor with six zinc-finger domains that is differentially expressed during hemato- and lymphopoiesis. We show here that transcription from the Gfi1b gene locus is silenced in the spleen but not in the bone marrow of transgenic mice that constitutively express Gfi1b under the control of the pan-hematopoietic vav promoter. Sequence analysis of the Gfi1b promoter showed the presence of potential Gfi1/Gfi1b-binding sites close to the mRNA start site. The expression of reporter gene constructs containing the Gfi1b core promoter appended to the luciferase gene were strongly repressed in the presence of exogenous Gfi1b. Moreover, analysis of combinatorial mutant mice that carry the vav-Gfi1b transgene and a green fluorescent protein-tagged Gfi1 gene locus demonstrated that the Gfi1 gene can be repressed by Gfi1b. Direct binding of Gfi1b and Gfi1 to the potential binding sites in the Gfi1b promoter could be demonstrated by gel-shift analyses in vitro. Chromatin-immunoprecipitation experiments showed that both the Gfi1b and the Gfi1 promoter are indeed occupied by Gfi1b in vivo. Hence, we conclude from our data that Gfi1b can auto-repress its own expression, but, in addition, is also able to cross-repress expression of the Gfi1 gene most likely in a cell type specific manner.